Health systems organization for emergency care - Pedroto, Isabel (2013)
The increasing number of acute and severe digestive diseases presenting to hospital emergency departments, mainly related with an ageing population, demands an appropriate answer from health systems organization, taking into account the escalating pressure on cost reduction. However, patients expect and deserve a response that is appropriate, effective, efficient and safe. The huge variety of variables which can influence the evolution of such cases warranting intensive monitoring, and the coordination and optimization of a range of human and technical resources involved in the care of these high-risk patients, requires their admission in hospital units with conveniently equipped facilities, as is done for heart attack and stroke patients. Little information of gastroenterology emergencies as a function of structure, processes and outcome is available at the organizational level. Surveys that have been conducted in different countries just assess local treatment outcome and question the organizational structure and existing resources but its impact on the outcome is not clear. Most studies address the problem of upper gastrointestinal bleeding and the out-of-hours endoscopy services in the hospital setting. The demands placed on emergency (part of the overall continuum of care) are obvious, as are the needs for the efficient use of resources and processes to improve the quality of care, meaning data must cover the full care cycle. Gastrointestinal emergencies, namely gastrointestinal bleeding, must be incorporated into the overall emergency response as is done for heart attack and stroke. This chapter aims to provide a review of current literature/evidence on organizational health system models towards a better management of gastroenterology emergencies and proposes a research agenda.